Exploring the implementation of virtual reality technology for the assessment of daily living activities - Kauer Brazil, Cristiane (Kansas State University, 2022)
Virtual Reality (VR) technology has created many simulation possibilities that were once either physically unfeasible, too expensive, or risky to be executed in real-life. Researchers have been taking advantage of this technology to help older adults prolong independent living and increase their quality of life. With an increased number of older adults, a major concern relates to detecting disease-related cognitive decline, which can manifest itself in the form of impairments in the ability to perform daily living activities. Currently, those abilities are measured subjectively as performance-based tests are impractical to be conducted. VR technology has the potential to facilitate those tests and improve screening techniques. In testing for a real-life task with VR, it is imperative to understand the effect of using this technology so that task performance is the only variable being measured, and not the person’s ability to use the technology and/or technology limitations. So far, very limited research has explored the validity and fidelity of VR simulations for daily living activities in combination with the feasibility and acceptability of this technology by older adults. In this dissertation, implications of using VR technology to conduct assessments related to daily activities were evaluated. First, it was investigated how fine motor movements – an important component of daily living activities that has been understudied – replicate in VR with younger and older adults. A learning effect related to the technology was determined by having participants repeat the task in each real-life and in VR in a novel study design. Results showed high feasibility and acceptability of implementing the simulation with both groups and some limitations in fidelity related to longer times to complete the task in VR. No significant difference in number of errors was observed between real and virtual, as well as between younger and older adults. In a second VR study, it was evaluated if gaming experience and training protocols influenced performance for simple daily activities, as well as VR-specific tasks in a sample of younger adults. Gaming abilities were found transferable when using the VR, with participants that were classified as “gamers” taking less time to complete tasks. VR for simulation of daily activities was considered very intuitive, with majority of participants being able to complete the tasks even without any instruction on how to use the VR system. VR technology was found to be a feasible, intuitive, and acceptable tool to test for simple daily living activities and fine motor movements. The older adult sample could easily engage with the system and, with a little bit of practice, reduce the time gap in performance when compared to younger adults. The rising adherence of technology by older adults may also contribute to the acceptability of implementing new technologies as part of routine health exams. This will also reinforce the need to control for possible confounding factors, such as experience with video games, and keep exploring new ones as the technology evolves. Future studies using VR technology should incorporate findings from this dissertation to improve assessments with any age group and minimize bias in outcome variables of interest.
Keywords: Virtual reality; Aging; Activities of daily living; Acceptability; Validity